2008
DOI: 10.1039/b716558g
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for an iron(iv)-oxo porphyrin π-cation radical as an active oxidant in catalytic oxygenation reactions

Abstract: A high-valent iron(IV)-oxo porphyrin pi-cation radical is an active oxidant in the catalytic oxygenation of organic substrates by an iron(III) porphyrin complex and peracids, whereas an iron(III)-oxidant porphyrin adduct is a sluggish oxidant in iron porphyrin model reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 41 publications
0
37
0
2
Order By: Relevance
“…X-ray structural spectroscopy, electrospray ionization mass spectrometry (ESI-MS), electron paramagnetic resonance (EPR) spectroscopy, infrared spectroscopy and ultraviolet-visible (UV-vis) data supported the formation of 1 with a Fe þ3.5 -N-Fe þ3.5 core unit (Supplementary Figs S1-S7 and Tables S1 and S2) 25 . m-CPBA was chosen as the oxygen donor because the formation of mononuclear oxoiron(IV) porphyrin cation radical complexes using m-CPBA is well documented [17][18][19][20][21] . The first such compound was prepared using the iron 5, This complex was characterized by low-temperature UV-vis spectroscopy, cryospray mass spectrometry, as well as EPR and Mössbauer spectroscopies (Supplementary Figs S12-S15).…”
Section: Resultsmentioning
confidence: 99%
“…X-ray structural spectroscopy, electrospray ionization mass spectrometry (ESI-MS), electron paramagnetic resonance (EPR) spectroscopy, infrared spectroscopy and ultraviolet-visible (UV-vis) data supported the formation of 1 with a Fe þ3.5 -N-Fe þ3.5 core unit (Supplementary Figs S1-S7 and Tables S1 and S2) 25 . m-CPBA was chosen as the oxygen donor because the formation of mononuclear oxoiron(IV) porphyrin cation radical complexes using m-CPBA is well documented [17][18][19][20][21] . The first such compound was prepared using the iron 5, This complex was characterized by low-temperature UV-vis spectroscopy, cryospray mass spectrometry, as well as EPR and Mössbauer spectroscopies (Supplementary Figs S12-S15).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there is a growing need to examine the reactivity of Cpd 0 towards organic substrates in the course of direct oxidation reactions. A more recent study by Nam et al [8] has demonstrated that addition of a four-fold excess of m-chloroperbenzoic acid (m-CPBA) to [Fe III -(TMP)(Cl)] (TMP = meso-tetramesitylporphyrin) in mixed CH 3 CN/CH 2 Cl 2 at À40 8C affords the formation of [9] ) at À15 8C resulted in spectral changes that indicated the occurrence of a two step reaction. The first reaction step is characterized by a small but significant absorbance increase in the Soret band with a concomitant shift of about 1-2 nm to longer wavelength, and a substantial absorbance decrease in the range between 440 and 540 nm ( Figure 1).…”
Section: C)fementioning
confidence: 97%
“…[1,2] Deshalb besteht großes Interesse an der Reaktivität von Cpd 0 gegenüber organischen Substraten bei direkten Oxidationsreaktionen. Neueste Studien von Nam et al [8] [9] ) in Acetonitril bei À15 8C führt zu spektralen ¾nderungen, die auf eine zweistufige Reaktion hindeuten: Der erste Reaktionsschritt ist durch einen kleinen, aber signifikanten Anstieg der Soret-Bandenabsorbanz charakterisiert, der mit einer Verschiebung um 1-2 nm zu größeren Wellenlängen und einer deutlichen Abnahme der Absorbanz im Bereich zwischen 440 und 540 nm einhergeht (Abbildung 1). Darauf folgt eine langsamere Reaktion, die sich in einer großen Abnahme der Absorbanz an der Soret-Bande und einem Anstieg zwischen 550 und 700 nm niederschlägt.…”
Section: IVunclassified